Adult Nephroblastoma with Predominant Epithelial Component: A Differential Diagnostic Candidate of Papillary Renal Cell Carcinoma and Metanephric Adenoma—Report of Three Cases - Shiho Watanabe; Hiroshi Naganuma; Michio Shimizu; Satoshi Ota; Shin-ichi Murata; Naoki Nihei; Jun Matsushima; Shuji Mikami; Naoto Kuroda; Yoji Nagashima; Yukio Nakatani (Case Reports in Pathology)
Although nephroblastoma is the commonest renal tumor of childhood, it is rare in adults. In cases of predominantly epithelial type occurring in adulthood, it might be difficult to distinguish it from papillary renal cell carcinoma and metanephric adenoma. Here, we report three cases of adult epithelial nephroblastoma in 24-, 76-, and 21-year-old females. Histologically, the tumors were composed of papillotubular architectures of small and uniform tumor cells with high nucleocytoplasmic ratio without blastemal element. Immunohistochemically, the tumor cells were positive for WT-1 and CD57 but negative for AMACR, which was helpful to exclude the possibility of papillary renal cell carcinoma. Metanephric adenoma is a benign tumor, which can be distinguished by the observation of the cellular atypism and growth pattern. However, nephroblastoma with predominant epithelial element mimics the malignant counterpart of metanephric adenoma, that is, “metanephric adenocarcinoma.”